The Influence of Farmer Group Management on the Success of the Integrated Farming Programme - luthfia widi, Hana; Yuzen , Haani Haritsa; Azharah , Syerly Lia (Smart International Management Journal, 2024)
This study aims to explore the influence of farmer group management on the success of integrated farming programmes. A total of 500 respondents from 10 farmer groups in five sub-districts in Indonesia were selected based on criteria such as the type of commodity being cultivated, partnership patterns, and level of access to extension services. The research instrument was a structured questionnaire designed to measure the independent variables, namely aspects of farmer group management (planning, coordination, division of tasks, and evaluation), and the dependent variable, which includes productivity, sustainability, and member satisfaction. Descriptive analysis was used to describe the characteristics of respondents and the distribution of research variables, while inferential analysis was conducted using multiple linear regression. The results show that the majority of respondents rated the aspects of farming group management as good to very good. Coordination within farmer groups has a significant positive influence on the successful of the integrated farming programme (B = 0.28, p = 0.001). The results of this study are expected to serve as a foundation in the development of community-based policies to improve farmers' welfare and agribusiness sustainability in Indonesia